Strengthening the Competitive Image of Private Islamic Higher Educational Institutions in Indonesia as an Effective Marketing Material: The Mediating Role of Service Innovation - Riofita, Hendra (STI Policy and Management Journal, 2024)
This study is carried out to employ service innovation to trigger effective leader and employee involvement effect respectively on competitive image to respond highly competitive market in recruiting prospective students. This survey study takes the data processed with SPSS and Amos program using a questionnaire sent in the form of Google link to the elements of the leaders organizing Private Islamic Higher Educations in Indonesia. They are the respondents of this study taken using multi stage and simple random sampling method. The findings of this study show that service innovation triggers effective leader and employee involvement effect respectively on competitive image. Through the service innovation, effective leader and employee involvement can drive competitive image to be an effective marketing material to recruit prospective students. All constructs employed can manifest the role of institutional resources to compete as intended by resource-based view theory.    Keywords: Islam, leadership, service innovation, image, higher education